Typologies and determinants of coping responses to forage and water scarcity among livestock farmers in south-western Uganda: Does gender matter? - David Mfitumukiza; Ronald Twongyirwe; Gordon Y. Mwesigwa; Esther Kebirungi; Viola Nilah Nyakato; Consolata Kabonesa (Scientific African)
Context specific evidence, including understanding of gender–differentiated responses to shocks and stresses, could bolster adaptation and resilience building amongst agricultural communities, amidst a changing climate. However, information derived from such a perspective is currently deficient in livestock production literature. In this study, we use a gendered lens to assess responses of male– and female-headed livestock dependent households to drought–induced water and forage shortages in south-western Uganda. The study specifically addresses four questions: (i) What are the gender differentiated characteristics, and typologies of households involved in livestock production? (ii) How do the gender disaggregated household characteristics influence the perceived extent of effects of water and forage shortage? (iii) How do gender disaggregated household characteristics influence coping strategies to water and forage shortages? (iv) What are the gender–based roles in coping with water and forage shortages? Data were collected from livestock-dependent households using a semi-structured questionnaire. The data were analysed and presented using various techniques including descriptive and inferential statistics (e.g., principal components and cluster analyses, and ordered probit modelling). Results show that livestock production is persistently male-dominated, with female-headed households poorer and more likely to earn less (p < 0.05) from livestock farming than their male-headed counterparts. Female heads of households were about 10 years older than their male-head counterparts, but they are more likely to be widows or single (p < 0.05). Marital status and number of male employees were the most important factors for divergent views on the extent of water and forage shortage. Yet, household size and income were most important for coping with water and forage shortages. Coping with drought effects exhibited a gendered trend, and traditional gender roles in livestock management are changing. Our findings provide a basis for gender–responsive policy and practice interventions – in the changing contexts – for enhanced involvement of women in livestock production-based livelihoods.